Therapeutic Effects and Underlying Mechanism of SOCS-com Gene-Transfected ADMSCs in Pressure Ulcer Mouse Models - Youngsic Eom; So Young Eom; Jeonghwa Lee; Saeyeon Hwang; Jihee Won; Hyunsoo Kim; Seok Chung; Hye Joung Kim; Mi-Young Lee (Cells, 2023)
Although the proportion of ulcer patients with medical problems among the elderly has increased with the extension of human life expectancy, treatment efficiency is drastically low, incurring substantial social costs. MSCs have independent regeneration potential, making them useful in clinical trials of difficult-to-treat diseases. In particular, ADMSCs are promising in the stem cell therapy industry as they can be obtained in vast amounts using non-invasive methods. Furthermore, studies are underway to enhance the regeneration potential of ADMSCs using cytokines, growth factors, and gene delivery to generate highly functional ADMSCs. In this study, key regulators of wound healing, SOCS-1, -3, and -5, were combined to maximize the regenerative potential of ADMSCs in pressure ulcer treatments. After transfecting SOCS-1, -3, -5, and SOCS-com into ADMSCs using a non-viral method, the expression of the inflammatory factors TNF-alpha, INF-gamma, and IL-10 was confirmed. ADMSCs transfected with SOCS-com showed decreased overall expression of inflammatory factors and increased expression of anti-inflammatory factors. Based on these results, we implanted ADMSCs transfected with SOCS-com into a pressure ulcer mouse model to observe their subsequent wound-healing effects. Notably, SOCS-com improved wound closure in ulcers, and reconstruction of the epidermis and dermis was observed. The healing mechanism of ADMSCs transfected with SOCS-com was examined by RNA sequencing. Gene analysis results confirmed that expression changes occurred in genes of key regulators of wound healing, such as chemokines, MMP-1, 9, CSF-2, and IL-33, and that such genetic changes enhanced wound healing in ulcers. Based on these results, we demonstrate the potential of ADMSCs transfected with SOCS-com as an ulcer treatment tool.